2015
DOI: 10.1007/s11250-015-0948-7
|View full text |Cite
|
Sign up to set email alerts
|

Crude glycerin combined with sugar cane silage in lamb diets

Abstract: This study aimed to evaluate the effect of the level of crude glycerin (CG) on in vitro fermentation kinetics (0, 20, 40, 60, and 80 g/kg DM of sugar cane silage), on in vitro neutral detergent fiber (NDF) degradation (0, 30, 60, and 90 g/kg DM of sugar cane silage), and intake and digestibility of nutrients and nitrogen balance (0, 20, 55, 82, and 108 g/kg DM of sugar cane silage) in lambs. The in vitro trials were conducted in a completely randomized design with three repetitions. The in vivo trial was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Many studies have evaluated the use of CG in ruminant diets in terms of nitrogen balance (Oliveira et al, 2016), meat quality (Lage et al, 2014), fatty acid profile (Terré, Nudda, Casado, & Bach, 2011), milk composition (Paiva et al, 2016), and rumen metabolites (Barton et al, 2013); the origin and concentration of glycerol has resulted in different research outcomes. Limited information is available regarding the effects of dietary glycerol as part of flushing (the practice of increasing an animal's nutrient intake and body condition prior to and during breeding in an effort to increase its ovulation and fertilization rates) on ewes' performance during the reproductive season.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have evaluated the use of CG in ruminant diets in terms of nitrogen balance (Oliveira et al, 2016), meat quality (Lage et al, 2014), fatty acid profile (Terré, Nudda, Casado, & Bach, 2011), milk composition (Paiva et al, 2016), and rumen metabolites (Barton et al, 2013); the origin and concentration of glycerol has resulted in different research outcomes. Limited information is available regarding the effects of dietary glycerol as part of flushing (the practice of increasing an animal's nutrient intake and body condition prior to and during breeding in an effort to increase its ovulation and fertilization rates) on ewes' performance during the reproductive season.…”
Section: Introductionmentioning
confidence: 99%
“…This probably occurred because there was equilibrium and synchrony of protein and energy sources in the diets, which meant that the protein : energy ratio did not affect nitrogen retention. Although there was an increase in the glycerol concentration with the inclusion of crude glycerin in the lambs' diet, this increase does not seem to have negatively affected the growth of bacteria and, consequently, nitrogen retention, as when the glycerin quantity was elevated, no differences in the retained nitrogen quantity were observed (Oliveira Filho et al, 2016).…”
Section: Discussionmentioning
confidence: 84%
“…The difference in feedlot days between lambs that were not fed glycerin and those that were fed with 200 g kg −1 DM was 10 d. This increase in feedlot days was probably due to a decrease in the DM intake and weight gain. With the inclusion of glycerol in the diet of ruminants, increased propionate in the rumen is observed (Ribeiro et al, 2018); this increases adenosine triphosphate (ATP) production because of its use for glucose production and satiety signaling (Reynolds, 1995) and can contribute to a consequent decrease in the DM intake. Ribeiro et al (2018) found a decrease in the DM intake, final BW, and ADG of lambs fed diets with glycerin at 70, 140, and 210 g kg −1 DM, indicating the inclusion of up to 4.7 % crude glycerin in the diets.…”
Section: Discussionmentioning
confidence: 99%